Application of Single Minute Exchange Die (SMED) Method to Minimize Setup Time on 350T Capacity Molding Machine - Sumasto, Fredy; Arrofah, Muhammad Arif; Pratama, Indra Rizki; Purbaningrum, Sanurya Putri; Satria, Adam; Rapi, Amrin (LPPM Politeknik Aceh Selatan, 2025)
This study aims to apply the Single Minute Exchange of Die (SMED) method in reducing setup time on a 350T capacity molding machine at PT HMG. The data collection results showed that the frequency of mold changes reached 70 times a month, with the average time required for mold changes before the implementation of SMED 173 minutes. After the implementation of SMED, the mold change time was successfully reduced to 64 minutes, reflecting a decrease of 63%. The implementation of SMED was carried out through several stages, including converting internal activities to external ones, which aimed to reduce machine downtime. Optimization of the remaining activities was also carried out, such as reducing the temperature drop time on the barrel and hot runner, which previously took 15 minutes, now only 5 minutes. The final results showed that machine downtime cost savings reached Rp11,200,000 per month after the implementation of SMED, with total downtime costs decreasing from Rp30,274,999 to Rp19,074,999 per month. This study proves that implementing the SMED method can significantly improve time efficiency, reduce production costs, and create more efficient operational standards. The findings provide a solid basis for further development in industry manufacturing practices.